The Influence Of School Management On Teacher Performance - Nugroho, Zaki Azis; Sulaeman, Maryam (EDUCATIO : Journal of Education, 2022)
School Management is an activity carried out effectively and efficiently to improve school performance in achieving educational goals, both national goals and institutional goals, the results of which can be seen from several factors as indicators of the performance achieved by the school. School management is tasked with creating a learning schedule that will be implemented at school. Lesson schedules cannot be created haphazardly. A lesson schedule is required in every school. This type of research is quantitative research. The method used is descriptive analytical correlation aimed at finding whether there is an influence and if there is an influence, how much influence the school management has on the performance of teachers at Bina Pangudi Luhur Vocational School. In this study, the population was all 33 teachers at Bina Pangudi Luhur Vocational School, Jakarta. From the results of observations in the field, it is known that school management carried out by Bina Pangudi Luhur Vocational School teachers has an impact on teacher performance and determines the quality of teacher performance. Thus, this condition shows that school management has no significant effect on teacher performance variables. the same as the law of cause and effect, the better the learning management carried out by the principal and teachers of Bina Pangudi Luhur Vocational School, the better the teacher's performance in the learning process and the work results that can be achieved by a teacher in an educational institution in accordance with their duties and responsibilities.